STUDI KELAYAKAN USAHA DAN ANALISIS RESIKO LINGKUNGAN PENGOLAHAN LIMBAH PADAT IKAN PATIN (Pangasius hypopthalamus) - Hendrik Hendrik (Jurnal Ilmu Lingkungan, 2016)
Traditional and modern food processing derived from catfish, such as fish fillets, smoked, salted, nuggets, meatballs, shredded and others; generate solid waste such as meat tetelan, abdominal fat, liver, bone, head, fins and innards. These wastes account for about 20-60% and is considered as part of that do not have economic value. Whereas solid waste is still potential as a raw material that contains relatively high nutritional value. Thus the utilization of solid waste that can generate added value in the form of raw materials and feed fish food industry. Conversely, if the solid waste is not utilized, will surely disturb the surrounding environment, good for water, air, soil, and the surrounding population. At this time there is no productive business specializing in the utilization of solid waste from the processing of catfish into industrial raw materials of food and fish feed. The possibility of this was due to the unavailability of data and information adequate technical and economical. In order to meet the needs of the research that was conducted. This study aimed to analyze the economic valuation of the utilization of industrial solid waste processing of catfish, the raw material of functional food and feed that meet the quality standards in accordance with the National Standards Indonnesia (SNI) as well as to determine the recommendation whether it is feasible or not the establishment of the business of processing food and feed of waste Solid results catfish processing of household or industrial scale. This research is a lab-scale experiments using technology that has undergone several modifications. The results showed that the technology is capable of producing industrial raw materials in the form of Fish Protein Concentrate (KPI), fish oil, bone meal and pyloric caeca crude enzyme in accordance with the Indonesian National Standard. , Judging from the environmental impact assessment and business analysis Gross NPV Rp. 24.788.000, BCR 1.15, IRR of 65.91% ,PR of 2.607 , then the utilization of solid waste business establishment catfish processing household scale feasible.